2015
DOI: 10.5796/electrochemistry.83.80
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis on Water Transport in Alkaline Anion Exchange Membrane Fuel Cells

Abstract: We present an isothermal, one-dimensional, steady-state model for an alkaline anion exchange membrane fuel cell (AAEMFC), in which the conducting ions (OH − ) move from the cathode to the anode. While water is produced at the anode, it is consumed at the cathode along with oxygen. The water transport in the membrane comprises water flux by the electro-osmotic drag and the diffusive water flux because of the gradient of water concentration across the membrane. The present model is validated with the experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…A high-fidelity numerical model can potentially play a complementary role to experimental investigations, and can provide detailed insights into the interactions between the electrochemical mechanism, and heat and mass transport phenomena, which play pivotal roles in water management of AEM fuel cells. One-dimensional numerical analyses conducted by Sohn et al [25] reinforced the importance of the anode humidification in order to achieve better membrane performance. Results…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A high-fidelity numerical model can potentially play a complementary role to experimental investigations, and can provide detailed insights into the interactions between the electrochemical mechanism, and heat and mass transport phenomena, which play pivotal roles in water management of AEM fuel cells. One-dimensional numerical analyses conducted by Sohn et al [25] reinforced the importance of the anode humidification in order to achieve better membrane performance. Results…”
Section: Introductionmentioning
confidence: 98%
“…suggested that under dry anode condition, the overall fuel cell performance was significantly negatively affected [25]. Numerical and experimental analyses were conducted in order to evaluate the deviated concentration loss in alkaline AEM fuel cells [26].…”
Section: Introductionmentioning
confidence: 99%
“…Given the potential fuel flexibility of AAEM fuel cells, and the necessity to develop alternative nonalcoholic anodic fuel (to avoid the presence of CO 2 from complete oxidation of alcohols), the developments in the field of hydrazine oxidation are briefly reported here. Further, water management in an AAEM fuel cell MEA is critical since ineffective operating conditions is suggested to lead to anode flooding where water is generated and cathode dry-out where water is stoichiometrically consumed. , In the cathode, poor water management leads to increases in both charge transfer resistance and hydroxide-anion transport. The subject of water management in AAEM fuel cells is beyond the scope of this review.…”
Section: Introductionmentioning
confidence: 99%
“…Y.-J. Sohn et al simulation studies further revealed that anode humidification was crucial for optimum AEMFC performance [158]. They observed only marginal loss in performance when AEMFC was simulated with dry cathode and fully humidified anode while dry anode and fully humidified cathode showed a significant loss in performance.…”
Section: Effect Of Relative Humiditymentioning
confidence: 98%